2018
DOI: 10.1002/slct.201801089
|View full text |Cite
|
Sign up to set email alerts
|

Water‐PEG‐400 Mediated an Efficient One‐Pot Eco‐Friendly Synthesis of Functionalized Isoxazole Substituted Chromeno[2, 3‐b]pyridine‐3‐carboxylate Derivatives

Abstract: A green, straightforward, and efficient protocol for the synthesis of a new series of isoxazolyl chromeno[2, 3-b]pyridine-3carboxylate derivatives have been reported by one-pot reaction of isoxazolyl enamino esters and 3-formylchromones by employing water as a reaction medium and polyethylene glycol-400 (PEG-400) as the green promoter. The superiority of this protocol is environmentally benign, simple operation, metal-free, broad substrate scope, good yields, less reaction time and PEG-400 can be recovered and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Further optical studies proceeded, and the results indicated that this scaffold could be tuned to enhance its photochemical properties, to be used as a photodetector. Ponduri et al explored the reactivity of isoxazolyl enamino esters 57 with 3formylchromones 53 to generate new chromenopyridine-based compounds 58 (Scheme 8B) [71]. Optimization of the reaction conditions showed that water was the best solvent, while the use of PEG-400 (10% mol) catalysis at 100 °C was also optimal.…”
Section: Chromonesmentioning
confidence: 99%
“…Further optical studies proceeded, and the results indicated that this scaffold could be tuned to enhance its photochemical properties, to be used as a photodetector. Ponduri et al explored the reactivity of isoxazolyl enamino esters 57 with 3formylchromones 53 to generate new chromenopyridine-based compounds 58 (Scheme 8B) [71]. Optimization of the reaction conditions showed that water was the best solvent, while the use of PEG-400 (10% mol) catalysis at 100 °C was also optimal.…”
Section: Chromonesmentioning
confidence: 99%
“…However, solvent plays a prime part in organic reactions by providing a homogeneous mixture and enhancing molecular contacts. To overcome the concerns and developing efficient catalyst systems, using water as a reaction medium is highly desirable in terms of environmentally benign and atom economy.…”
Section: Introductionmentioning
confidence: 99%